Study on the Bond Performance of Epoxy Resin Concrete with Steel Reinforcement - Peiqi Chen; Yueqiang Li; Xiaojie Zhou; Hao Wang; Jie Li (Buildings)
Epoxy resin concrete, characterized by its superior mechanical properties, is frequently utilized for structural reinforcement and strengthening. However, its application in structural members remains limited. In this paper, the bond–slip behavior between steel reinforcement and epoxy resin concrete was investigated using a combination of experimental research and finite element analysis, with the objective of providing data support for substantiating the expanded use of epoxy resin concrete in structural members. The research methodology included 18 center-pullout tests and 14 finite element model calculations, focusing on the effects of variables such as epoxy resin concrete strength, steel reinforcement strength, steel reinforcement diameter and protective layer thickness on bond performance. The results reveal that the bond strength between epoxy resin concrete and steel reinforcement significantly surpasses that of ordinary concrete, being approximately 3.23 times higher given the equivalent strength level of the material; the improvement in the strength of both the epoxy resin concrete and steel reinforcement are observed to marginally increase the bond stress. Conversely, an increase in the diameter of the steel reinforcement and a reduction in the thickness of the protective layer of the concrete can lead to diminished bond stress and peak slip. Particularly, when the steel reinforcement strength is below 500 MPa, it tends to reach its yield strength and may even detach during the drawing process, indicating that the yielding of the steel reinforcement occurs before the loss of bond stress. In contrast, for a steel reinforcement strength exceeding 500 MPa, yielding does not precede bond stress loss, resulting in a distinct form of failure described as scraping plough type destruction. Compared to ordinary concrete, the peak of the epoxy resin concrete and steel reinforcement bond stress–slip curve is more pointed, indicating a rapid degradation to maximum bond stress and exhibiting a brittle nature. Overall, these peaks are sharper than those of ordinary concrete, indicating a rapid decline in bond stress post-peak, reflective of its brittle characteristics.